The Cambridge centennial edition of The great Gatsby - Fitzgerald, F. Scott 1896-1940 (Cambridge University Press, 2025)
The Great Gatsby is often called the great American novel. Emblematic of an entire era, F. Scott Fitzgerald's classic tale of illicit desire, grand illusions, and lost dreams is rendered in a lyrical prose that revives a vanished world of glittering parties and vibrant jazz, where money and deceit walk hand in hand. Rich in humor, sharply observant of status and class, the book tells the story of Jay Gatsby's efforts to keep his faith - in money, in love, in all the promises of America - amid the chaos and conflict of life on Long Island's Gold Coast during the Roaring Twenties. This centennial edition presents the established version of the text in a collector's volume replete with social, cultural, and historical context, and numerous illustrations. The authoritative introduction examines persistent myths about Fitzgerald, his greatest work, and the age he embodies, while offering fresh ways of reading this iconic work
Title from publisher's bibliographic system (viewed on 28 Jan 2025)
Keywords: Rich people / Fiction; Married women / Fiction; First loves / Fiction; Long Island (N.Y.) / Fiction